2017
DOI: 10.1139/cjpp-2016-0561
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of resveratrol on steatosis and mitochondrial oxidative stress in HepG2 cells

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently one of the most common chronic liver diseases, especially in developed countries. One group of substances with a potential use in the treatment of NAFLD are plant polyphenols, represented by resveratrol. The aim of this study was to evaluate the effect of resveratrol on steatosis and oxidative stress in HepG2 cells. The steatosis of cells was carried out using free fatty acids: oleic or palmitic acid and their mixtures. Steatosis was visualized using the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Studies have shown that resveratrol has a wide range of effects, including antimicrobial , anti‐inflammatory , antiapoptotic , and anticancer effects, and promotes osteogenic factor formation . Resveratrol can also play a beneficial role in liver diseases and hepatic steatosis by reducing oxidative stress and hepatic fibrosis . In addition, resveratrol has antioxidant effects on certain chronic diseases such as diabetes and cardiovascular disease .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that resveratrol has a wide range of effects, including antimicrobial , anti‐inflammatory , antiapoptotic , and anticancer effects, and promotes osteogenic factor formation . Resveratrol can also play a beneficial role in liver diseases and hepatic steatosis by reducing oxidative stress and hepatic fibrosis . In addition, resveratrol has antioxidant effects on certain chronic diseases such as diabetes and cardiovascular disease .…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies showed that resveratrol decreased steatosis in HepG2 cells induced by fatty acids mixtures and reduced the mitochondrial oxidative stress in cells. We also observed the favorable effect of resveratrol on the mitochondrial membrane potential in HepG2 cells treated with the mixtures of fatty acids (34).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the levels of antioxidant enzyme activity in the liver, such as SOD, GSH-Px, and CAT, are the indices of the antioxidative stress response [26]. Many natural products, such as Asiatic acid, apigenin, and resveratrol, can improve NAFLD by alleviating oxidative stress [27][28][29].…”
Section: Resultsmentioning
confidence: 99%